CTLA-4 and PD-1 combined blockade therapy for malignant melanoma brain metastases: mechanisms, challenges, and prospects - Wang, Jia-Wen; Feng, Ying-Fa; Liu, Jia-Hui (Frontiers in Immunology, 2025)
Malignant melanoma brain metastases (MBM) represent one of the deadliest complications of melanoma, with an incidence rate of 7.3%. Among patients with acral and mucosal melanoma, the cumulative 5-year incidence can reach 19.5%, accompanied by poor prognosis. The blood-brain barrier (BBB), an immunosuppressive central nervous system (CNS) microenvironment, and tumor immune evasion collectively limit the efficacy of traditional therapies. Cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and programmed cell death protein 1 (PD-1), as critical immune checkpoints, play pivotal roles in the progression of MBM. This study systematically analyzes the synergistic mechanisms, clinical outcomes, and challenges of CTLA-4 and PD-1 combined blockade therapy in MBM. The findings indicate that this combination therapy leverages a “priming and boosting” biological mechanism: CTLA-4 blockade broadens T-cell responses during the initial activation phase, while PD-1 blockade sustains T-cell activity during the effector phase, significantly improving intracranial response rates (46%, compared to 20% for monotherapy). Furthermore, the combination therapy increases the CD8+/Treg ratio and promotes memory CD8+ T-cell formation, enabling durable antitumor immune surveillance. However, challenges such as a 54% incidence rate of grade 3–4 adverse events and suboptimal therapeutic regimens remain. To address these issues, this study proposes a multi-tiered adverse event management system, personalized risk assessment models, and treatment optimization strategies based on real-time monitoring and dynamic adjustments. Future directions include developing precision stratified therapies based on immunogenomics, exploring multi-target synergistic approaches, and implementing intelligent adverse event prediction and management systems to maximize therapeutic efficacy and minimize toxicity, providing more effective treatment for MBM patients.